Sistem Penjadwalan Kuliah Berbasis Click and Drag (Studi Kasus di Fakultas Sains & Teknologi Universitas Teknologi Yogyakarta) - Shoffan Saifullah; Arief Hermawan (Maranatha University Press, 2017)
Utilization of technology in education is very important, especially at the University of Technology in Yogyakarta, which is one of the private universities in Yogyakarta with several objectives, one which is utilizing the maximum potential of technology to improve the effectiveness and efficiency of learning and dissemination of science and technology. One factor that can improve academic services are scheduling a lecture. Making a schedule of lectures is not an activity that is easy to do, because in doing scheduling not only arrange the schedule between subjects, time, lecturers and rooms. College scheduling systems currently running is less effective, because it requires a long time, and often clashes at student schedules. In this research, system development, scheduling lectures at the Faculty of Science and Technology, University of Technology Yogyakarta, where the scheduling system, click and drag more easily and to minimize clashes class schedules.